2013
DOI: 10.1111/conl.12058
|View full text |Cite
|
Sign up to set email alerts
|

Oil Palm and Deforestation in Papua New Guinea

Abstract: An unprecedented increase in oil palm developments may be underway in Papua New Guinea (PNG) through controversial "special agricultural and business leases" (SABLs) covering over two million hectares. Oil palm development can create societal benefits, but doubt has been raised about whether the SABL developers intend establishing plantations. Here, we examine the development objectives of these proposals through an assessment of their land suitability, developer experience and capacity, and sociolegal constra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 27 publications
(60 reference statements)
2
57
0
Order By: Relevance
“…In other words, villagers in Jambi do not clear forest with the immediate intention to use the land for oil palm. This is in line with a study in Papua New Guinea, where Nelson et al (2013) concluded that deforestation takes place without an explicit intention to grow oil palm in the future. On the other hand, the results in column (3) show that oil palm cultivation and fallow land in the past both contributed to declining forest land at the village level.…”
Section: Base Model Estimation Resultssupporting
confidence: 90%
“…In other words, villagers in Jambi do not clear forest with the immediate intention to use the land for oil palm. This is in line with a study in Papua New Guinea, where Nelson et al (2013) concluded that deforestation takes place without an explicit intention to grow oil palm in the future. On the other hand, the results in column (3) show that oil palm cultivation and fallow land in the past both contributed to declining forest land at the village level.…”
Section: Base Model Estimation Resultssupporting
confidence: 90%
“…Most of the plantations operated by the existing two palm oil-producing companies are on land alienated during the time of the Australian administration, although they also operate some 'mini-estates' on land subleased from groups of customary landowners holding SABLs (see Chapter 6, this volume). The two oil palm companies started making use of these lease arrangements in the late 1990s, but the amount of land they acquired through this process is only a tiny fraction of the area of more than 5 million hectares allocated to other companies under SABLs issued since 2003 (Filer 2011(Filer , 2012aMoore 2011;Winn 2012;Nelson et al 2014). Most of this land has been subleased to foreign investors, which has caused an outpouring of frustration and anger among rural people in many parts of the country about the loss of rights to their land and resources (Mirou 2013;Mousseau 2013;Numapo 2013).…”
Section: Land Acquisitions For Oil Palm Developmentmentioning
confidence: 99%
“…While the main justification for the scale of alienation was the establishment of large-scale commercial agricultural ventures, it is now clear that many of the development agreements were being used as a pretext for logging, with many developers having no experience or interest in establishing the agricultural industries promised in the agreements (Nelson et al 2010(Nelson et al , 2014Filer 2011;Winn 2012). Developer applies to PNG Forest Authority (PNGFA) for forest clearing authority (FCA) .…”
Section: Land Acquisitions For Oil Palm Developmentmentioning
confidence: 99%
“…Most of the plantations operated by the existing two palm oil-producing companies are on land alienated during the time of the Australian administration, although they also operate some 'mini-estates' on land subleased from groups of customary landowners holding SABLs (see Chapter 6, this volume). The two oil palm companies started making use of these lease arrangements in the late 1990s, but the amount of land they acquired through this process is only a tiny fraction of the area of more than 5 million hectares allocated to other companies under SABLs issued since 2003 (Filer , 2012aMoore 2011;Nelson et al 2014). Most of this land has been subleased to foreign investors, which has caused an outpouring of frustration and anger among rural people in many parts of the country about the loss of rights to their land and resources Numapo 2013).…”
Section: Land Acquisitions For Oil Palm Developmentmentioning
confidence: 99%
“…While the main justification for the scale of alienation was the establishment of large-scale commercial agricultural ventures, it is now clear that many of the development agreements were being used as a pretext for logging, with many developers having no experience or interest in establishing the agricultural industries promised in the agreements (Nelson et al 2010(Nelson et al , 2014). Developer applies to PNG Forest Authority (PNGFA) for forest clearing authority (FCA) .…”
Section: Land Acquisitions For Oil Palm Developmentmentioning
confidence: 99%